Investigation of the distribution and Fe content of iron sand at Wari Ino beach Tobelo using resistivity method with werner-schlumberger configuration - Sadjab, Bayu Achil; Indrayana, I Putu Tedy; Iwamony, Steven; Umam, Rofiqul (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
This research aimed to investigate the distribution, volume, and concentration of iron sand at Wari Ino Beach Tobelo. The resistivity method with Werner-Schlumberger configuration was applied to investigate the iron sand distribution. The measurements were set-up on 3 lines that run parallel along the coast of Wari Ino Village. The length of each trajectory was 150 meters with a spacing of 10 meters for each electrode. Data acquisition was carried out by using geoelectric instruments to obtain current injection (I) and voltage (V). The analysis was carried out by using RES2DINV and ROCKWORK software to obtain 2-D and 3-D cross-section models for interpreting the distribution and volume of the iron sand. The analysis and interpretation were supported by geological data of the location. Furthermore, the Fe content was characterized by using X-Ray Fluorescence Spectroscopy (XRF). There results show that the volume of the iron sand in each trajectory was 109,355 m3; 180,254 m3; and 120,556 m3. The total volume of iron sand along the three trajectories was up to 405,335 m3. The Fe content in the form of a free element is 67.41%, 57.12%, and 73.40%. The Fe content in the form of hematite mineral (Fe2O3) was 57.92%, 45.82%, and 65.47%.